Describing post-mortem characteristics of bovine congestive heart failure and evaluating variability of ionophore concentrations in feed delivered to feedyard cattle - Long, Katie Anne (My University, 2025)
Bovine congestive heart disease (CHF) has garnered the attention of both veterinarians and beef cattle producers, raising concerns regarding animal health, welfare, and economics. The exact cause of non-infectious right-sided CHF is not well known. Published data suggest a variety of factors such as genetics, concurrent pulmonary diseases, and other demographics play a role in the onset of CHF. To further complicate matters, CHF clinical case definition varies among feedyards, leading to potential misclassifications. Progressive right-ventricular remodeling leading to cardiomegaly, is a hallmark of CHF. Cardiac eccentric hypertrophy occurs following increased pre-load volume, leading to a dilated ventricle, increased myocardial mass, and increased end-diastolic volume. These anatomical changes result in decreased cardiopulmonary functionality. The objective of this research was to refine bovine right-sided CHF diagnosis and improve post-mortem diagnostic approaches utilizing objective methods in combination with subjective methods, as well as evaluate variability of ionophore concentrations in feed. This thesis delves into associations of objective and subjective post-mortem heart evaluations with the presence of CHF. Digital photographs and CHF diagnoses were acquired from an observational cross-sectional study on feedyard cattle mortalities. Digital cardiac photographs were measured in several locations to determine potential changes in heart size. Systemic post-mortem evaluations of 346 feedyard mortalities resulted in 106 cases being classified with cardiac enlargement/misshapen ventricle (CEMV). The CEMV cases were determined based on gross evaluation of heart size and shape with no signs of infectious heart disease present. A subset of CEMV cases were determined to be CHF when cases included congested (nutmeg) liver and at least two of the following lesions: serous or serosanguineous pleural, peritoneal, or pericardial effusion. Eleven of the 346 mortalities were classified as CHF. Descriptive statistics and multivariate models were used to identify associations between objective heart measurements and subjective heart scores with the prevalence of CEMV or CHF. The CEMV model showed heart width, left ventricular thickness, and right ventricular lumen area significantly associated with the prevalence of CEMV cases (p<0.05). Heart scores were also associated with the prevalence of CEMV cases (p<0.01). In contrast, identifying associations between CHF and objective heart measurements and subjective heart was not possible because the CHF model did not converge. Heart measurements and scores can be used to improve diagnosis of heart disease post-mortem and provide further insight into subclinical heart disease. An additional retrospective case-control study was conducted to determine potential differences in cardiac and hepatic histopathology between CHF cases and feedyard mortalities from other causes. Post-mortem examination was performed and samples retrieved from animals with grossly abnormal and normal hearts. Case-definition for CHF included abnormal heart shape, congested liver, and presences of ancillary signs; all other cases were considered as non-CHF for comparison. Cardiac and hepatic histopathology was performed categorizing fibrosis and necrosis into either none/minimal or moderate/severe changes. A generalized linear model was used to evaluate potential associations between the probability of CHF with histopathological lesions. Of the 87 cases included for analysis, 11 met the case definition for CHF. Cardiac histopathologic changes were identified in grossly normal and abnormal hearts with moderate/severe necrosis in 14.9% of mortalities and 16.1% moderate/severe fibrosis of mortalities. Hepatic necrosis was moderate/severe in 33.3% of mortalities and hepatic fibrosis was moderate/severe in 16.1% of mortalities. Liver fibrosis was the only factor associated with CHF probability and cattle with moderate/severe liver fibrosis were more (P < 0.01) likely (0.57 +/- 0.13) to have CHF compared to cattle with minimal liver fibrosis (0.04 +/- 0.02). These results illustrate cardiac histopathologic changes were relatively rare and not associated with the probability of abnormal heart shape; however, hepatic histopathology may be useful in confirming CHF. This thesis further investigated potential external contributors to CHF in cattle, such as the potential role of ionophore toxicosis. Ionophores are a class of antibiotics commonly added to feed in commercial cattle feeding operations to act as a coccidiostat and increase feed efficiency. In high concentrations, ionophores can cause acute cardiotoxic effects in cattle, resulting in clinical signs similar to CHF. The first objective of this study was to evaluate the differences in the mean and variation of monensin concentrations between bunk location (at-delivery and 2 hours post-delivery), and between the batch location (beginning and end of batch as delivered from feed truck) to evaluate finisher ration samples from feedyards. One truck load was considered a batch and consisted of four feed samples (A, B, C, and D) from one central Kansas feedyard on eight different days. Sample points A and B were collected from the feed bunk at the initial time of feed delivery from the point where the truck began unloading (A) and where the truck finished unloading (B). Sample points C and D were collected from the same feed bunk 2 hours after-delivery from the point where the truck began unloading (C) and where the truck finished unloading (D). The second objective was to evaluate associations of feedyard diet particle size with monensin concentrations. Particle size distribution of starter and finisher ration samples were determined using a Penn State particle separator with four sieves (S1 = 0.75, S2 = 0.31, S3 = 0.16, S4 = <0.16). All samples were analyzed for monensin concentrations using Ultra Performance Liquid Chromatography (UPLC). Descriptive statistics were conducted on monensin concentrations and variability between samples and two multivariate models were used to identify associations between monensin concentrations in 1) batch or bunk location and 2) sieve location or ration type. There was no interaction between delivery timing and start or end of the batch; however, batch location affected monensin concentration in that the start of the batch had a higher (32,934 ± 18,982; mean ± SD) monensin concentration compared to the end of the batch (28,185 ± 17,560). In the second model, there was an interaction between sieve and ration type (P<0.01). The monensin concentrations in both starter (7,122 ± 3,477) and finisher (9,638 ± 4,705) rations were lower in S1. The monensin concentrations in both starter (25,837 ± 12,613) and finisher (18,384 ± 8,975) rations were highest in S4. These results show that monensin concentrations in feed samples can have important variability. These projects demonstrated the utility of objective heart measurements, subjective scoring systems, and liver histopathology in further refining the bovine right-sided CHF definition for feedlot cattle. Utilizing gross pathological findings, histopathologic findings, and monensin concentration variability, these useful approaches provide data that help fill the information gaps related to bovine right-sided CHF. This work warrants further research and lays a foundation for future hypotheses like evaluating objective post-mortem diagnosis and identification of risk factors for CHF.
Keywords: Feedyard; Cattle; Heart disease; Congestive heart failure; Necropsy